Incidence and factors associated with outcomes of uterine rupture among women delivered at Felegehiwot referral hospital, Bahir Dar, Ethiopia: cross sectional study - Dawud Muhammed Ahmed; Tesfaye Setegn Mengistu; Aemiro Getu Endalamaw (BMC, 2018)
Abstract Background Maternal mortality is a major public health challenge in Ethiopia. Uterine rupture is an obstetrical emergency with serious undesired complications for laboring mothers resulting in fatal maternal and neonatal outcomes. Uterine rupture has been contributing to high maternal morbidity and mortality. However, there is limited research on the factors and management outcomes of women with uterine rupture. Understanding the factors and management outcomes might delineate strategies to support survivors. Therefore the aim of this study is to assess the incidence and factors associated with outcomes of uterine rupture among laboring mothers at Felegehiwot Referral Hospital in Bahir Dar City, Northwest Ethiopia. Methods This is a cross sectional study with retrospective facility based data collection technique. All pregnant women who were managed for ruptured uterus at Felegehiwot referral hospital from September 11 2012 to August 30 2017 were included. The chart numbers of the women collected from operation theatre registers. Their case folders retrieved from the medical records room for analysis. Using structured check list, information on their sociodemography, booking status, clinical features at presentation and the place of attempted vaginal delivery was extracted. Data on the intraoperative findings, treatment, and associated complications and outcomes also collected. The collected data cleaned, coded and entered into EPI- Info version (7.1.2.0) and then exported in to SPSS Version 20.0 for analysis. Statistical comparison was done using chi square (X2). Strength of association between the explanatory variables and outcome variables described using odds ratio at 95% CI and P value less than 0.05. The results presented in tables. Results We studied 239 cases of uterine rupture in the 5 years period. Mothers without previous cesarean delivery including eight primigravidas took 87% of the cases. From all study participants, 54 of mothers (22.6%) developed undesired outcomes whereas 185(77.4%) discharged without major sequel. More than half (56.9%) arrived in hypovolemic shock. Total abdominal hysterectomy was the commonest procedure accounting for 61.5%. Duration of surgery was less than 2 h in 67.8% of the procedures. Anemia is the commonest complication (80.3%) followed by wound infection and VVF (11.7% each). There were 5 maternal deaths (2.1%). Mothers who had prolonged operation time (> 2 h) (AOR: 2.2, 95% CI: 1.10, 4.63) were significantly associated with undesired maternal outcomes after management of uterine rupture. Conclusion Incidence of ruptured uterus and its complications were high in the study area. It reflects the need for improvement in obstetric care and strong collaboration with referring health facilities to ensure prompt referral and management.